2022
DOI: 10.15252/emmm.202217175
|View full text |Cite
|
Sign up to set email alerts
|

Aged lipid‐laden microglia display impaired responses to stroke

Abstract: Microglial cells of the aged brain manifest signs of dysfunction that could contribute to the worse neurological outcome of stroke in the elderly. Treatment with colony‐stimulating factor 1 receptor antagonists enables transient microglia depletion that is followed by microglia repopulation after treatment interruption, causing no known harm to mice. We tested whether this strategy restored microglia function and ameliorated stroke outcome in old mice. Cerebral ischemia/reperfusion induced innate immune respon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 76 publications
0
25
1
Order By: Relevance
“…Aged microglia accumulate LDs and adopt a pro-inflammatory state (Marschallinger et al, 2020). The presence of these lipid-laden microglia correlates with an impaired response to stroke in aged mice (Arbaizar-Rovirosa et al 2023). Although it remains to be determined whether APOE can traffic to LDs in microglia, we speculate that LD-associated APOE4 in microglia could also play a key role in AD pathology.…”
Section: Discussionmentioning
confidence: 87%
“…Aged microglia accumulate LDs and adopt a pro-inflammatory state (Marschallinger et al, 2020). The presence of these lipid-laden microglia correlates with an impaired response to stroke in aged mice (Arbaizar-Rovirosa et al 2023). Although it remains to be determined whether APOE can traffic to LDs in microglia, we speculate that LD-associated APOE4 in microglia could also play a key role in AD pathology.…”
Section: Discussionmentioning
confidence: 87%
“…The accumulation of d-LDs is exacerbated in the microglia of old individuals driving an exaggerated type I IFN immune response and worsening the neurological outcome. 159 Hence, the equilibrium between f-and d-LDs could be somehow disrupted in unhealthy cells and contribute to pathogenesis.…”
Section: Toxoplasma Gondimentioning
confidence: 99%
“…157,158 For example, we have recently observed that after brain ischemia LDs accumulate in microglia, a population of immune cells residing in the brain. 159 These LDs resemble d-LDs and contain ISGs such as viperin, ISG15, RNF213, IFI47, TGTP1, IIGP1, and GBP6. After a stroke in elderly patients, the accumulation of d-LDs is exacerbated with a concomitantly aggravated type I IFN immune response that worsened the neurological outcome.…”
Section: Box 6 Interferons In Innate Immunitymentioning
confidence: 99%
See 2 more Smart Citations